Searching for Natural Aurora a Kinase Inhibitors from Peppers Using Molecular Docking and Molecular Dynamics - Paweł Siudem; Łukasz Szeleszczuk; Katarzyna Paradowska (MDPI AG, 2023)
Natural products are the precursors of many medicinal substances. Peppers (Piper, Capsicum, Pimienta) are a rich source of compounds with potential multidirectional biological activity. One of the studied directions is antitumor activity. Little research has been carried out so far on the ability of the compounds contained in peppers to inhibit the activity of Aurora A kinase, the overexpression of which is characteristic of cancer development. In this study, molecular docking methods, as well as molecular dynamics, were used, looking for compounds that could inhibit the activity of Aurora A kinase and trying to determine whether there is a relationship between the stimulation of the TRPV1 receptor and the inhibition of Aurora A kinase. We compared our results with anticancer activity studied earlier on MCF-7 cell lines (breast cancer cells). Our research indicates that the compounds contained in peppers can inhibit Aurora A. Further in vitro research is planned to confirm the obtained results.